Implementasi Penggunaan Media Online untuk Meningkatkan Kemampuan Cerdas Bermedia Sosial pada Siswa SMA Negeri 5 Palu - Akifah, Andi; Antasari, Citra; Wulandari, Dwi Rohma (Madani: Jurnal Pengabdian Ilmiah, 2024)
Abstract: Generational differences are always an issue that needs to be discussed in society. Each generation has unique characteristics which then determine the ongoing communication process. Technological developments are occurring so rapidly, making it easier to access information. This service aims to measure the implementation of online media use to improve media savvy students at SMA Negeri 5 Palu. The method used is participatory action research. Where the target audience is SMA Negeri 5 Palu students, with a total of 33 people. The solution strategy that can be offered in this service is to carry out counseling regarding digital literacy for teenagers, as well as increasing students' understanding of using social media, both as part of self-expression and being smart in using social media. Keywords: New Media; Literacy; teenager; intelligent